Application of TonB-Dependent Transporters in Vaccine Development of Gram-Negative Bacteria - Wang, Jia; Xiong, Kun; Pan, Qu; He, Weifeng; Cong, Yanguang (Frontiers in Cellular and Infection Microbiology, 2021)
Multiple scarce nutrients, such as iron and nickel, are essential for bacterial growth. Gram-negative bacteria secrete chelators to bind these nutrients from the environment competitively. The transport of the resulting complexes into bacterial cells is mediated by TonB-dependent transporters (TBDTs) located at the outer membrane in Gram-negative bacteria. The characteristics of TBDTs, including surface exposure, protective immunogenicity, wide distribution, inducible expression in vivo, and essential roles in pathogenicity, make them excellent candidates for vaccine development. The possible application of a large number of TBDTs in immune control of the corresponding pathogens has been recently investigated. This paper summarizes the latest progresses and current major issues in the application.